Spatiotemporal Dynamics and Geodetic Mass Changes of Glaciers With Varying Debris Cover in the Pangong Region of Trans-Himalayan Ladakh, India Between 1990 and 2019 - Majeed, Ulfat; Rashid, Irfan; Najar, Nadeem Ahmad; Gul, Nafeeza (Frontiers in Earth Science, 2021)
Glaciers across the Himalayan arc are showing varying signs of recession. Glaciers in the eastern and western parts of the Himalayan arc are retreating more rapidly as compared to other regions. This differential retreat is often attributed to climatic, topographic, and geologic influences. The glaciers in the Trans-Himalayan region of Ladakh are believed to be relatively stable as compared to other parts of the western Himalaya. The present study ascertained the area changes and frontal retreat of 87 glaciers in the Pangong Region between 1990 and 2019 using satellite data. The geodetic mass changes were also assessed using SRTM and TanDEM-X digital elevation models (DEMs) of 2000 and 2012 respectively. Besides, the glacier outlines were delineated manually and compared with existing regional and global glacier inventories that are available over the region. The GlabTop model was used to simulate the glacier-bed overdeepenings of 4 glaciers that are associated with a proglacial lake. The study also analyzed the impact of topographic influences and varying debris cover on glacier recession. This analysis indicated a deglaciation of 6.7 ± 0.1% (0.23% a-1) from 1990-2019 over the Pangong Region with clean-ice glaciers showing a higher retreat (8.4 ± 0.28%) compared to the debris-covered glaciers (5.7 ± 0.14%). However, the overall recession is lower compared to other parts of northwestern Himalayas. The glacier recession showed a positive correlation with mean glacier slope (r=0.3) and debris cover (r=0.1) with bigger size glaciers having retreated at a lesser pace compared to smaller ones. This underpins the need for in-situ data about debris thickness to precisely ascertain the role of debris on glacier recession in the Trans-Himalayan Ladakh where debris thickness data are absent. The mean glacier elevation did not indicate any influence on glacier recession. From 2000-12, the glaciers lost an ice mass amounting to 0.32 33 ± 0.4 05 m w.e. per year. The formation of 4 new proglacial lakes, although small (<6 ha), need to be monitored using remote sensing data while the infrastructure development activities should not be permitted given glacial lake outburst flood risk.